Aquifer imaging with pressure waves—Evaluation of low‐impact characterization through sandbox experiments. Issue 3 (24th March 2016) - Zhou, YaoQuan; Lim, David; Cupola, Fausto; Cardiff, Michael
Abstract: Understanding the detailed spatial variation of hydraulic properties in the subsurface has been the subject of intensive research over the past three decades. A recently developed approach to characterize subsurface properties is hydraulic tomography, in which a series of pumping tests are jointly inverted using a heterogeneous numerical model. Recently, Cardiff et al. (2013) proposed a modified tomography approach named Oscillatory Hydraulic Tomography (OHT), in which periodic pumping signals of different frequencies serve as the aquifer stimulation, and pressure responses are recorded at observation locations for tomographic analysis. Its key advantages over traditional hydraulic tomography are that: (1) there is no net injection or extraction of water, and (2) the impulse (an oscillatory signal of known frequency) is easily extracted from noisy data. However, OHT has only been evaluated through numerical experiments to date. In this work, we evaluate OHT performance by attempting to image known heterogeneities in a synthetic aquifer. An instrumented laboratory sandbox is filled with material of known hydraulic properties, and we measure aquifer responses due to oscillatory pumping stimulations at periods of 2, 5, 10, and 20 s. Pressure oscillation time series are processed through Fourier Transforms and inverted tomographically to obtain estimates of aquifer heterogeneity, using a fast, steady‐periodic groundwater flow model. We show that OHT is able to provide robust estimates of aquifer hydraulic conductivity even in cases where relatively few pumping tests and observation locations are available. The use of multiple stimulation frequencies is also shown to improve imaging results. Key Points: Laboratory evaluation of Oscillatory Hydraulic Tomography Provides robust estimates of aquifer hydraulic conductivity Multiple stimulation frequencies improve imaging results